2021
DOI: 10.1093/infdis/jiab425
|View full text |Cite
|
Sign up to set email alerts
|

Critically Ill Coronavirus Disease 2019 Patients Exhibit Hyperactive Cytokine Responses Associated With Effector Exhausted Senescent T Cells in Acute Infection

Abstract: COVID-19 can progress to severe pneumonia with respiratory failure and is aggravated by the deregulation of the immune system causing an excessive inflammation including the cytokine storm. We herein report that severe acutely infected patients have high levels of both type-1 and type-2 cytokines. Our results show abnormal cytokine levels upon T cell stimulation, in a non-polarized profile. Furthermore, our findings indicate that this hyperactive cytokine response is associated with a significantly increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…In mild/asymptomatic cases, SARS-CoV-2-specific T cells are polyfunctional and produce multiple cytokines(18); conversely, during severe disease, polyfunctional virus-specific T cells are underrepresented and are skewed towards a cytotoxic phenotype(19). Although SARS-CoV-2-specific T cells are protective in most cases, it has been shown they can contribute to the cytokine release syndrome seen in patients with severe COVID-19(20). Furthermore, CD8 + T cells in the lung during acute infection are associated with inflammation, fibrosis, biomarkers of vascular injury, and poor outcomes(21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…In mild/asymptomatic cases, SARS-CoV-2-specific T cells are polyfunctional and produce multiple cytokines(18); conversely, during severe disease, polyfunctional virus-specific T cells are underrepresented and are skewed towards a cytotoxic phenotype(19). Although SARS-CoV-2-specific T cells are protective in most cases, it has been shown they can contribute to the cytokine release syndrome seen in patients with severe COVID-19(20). Furthermore, CD8 + T cells in the lung during acute infection are associated with inflammation, fibrosis, biomarkers of vascular injury, and poor outcomes(21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…8B). In fact, those two epitopes have their slopes S the closest to 0 among all epitopes (Supplemental (ii) a general lymphopenia (11)(12)(13)(14)(15)(16); and (iii) a broad (not SARS-CoV-2-specific T cell exhaustion and/or impaired function (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). This was reported for immune cells both in the peripheral compartment (PBMCs) and in the lung and brain of symptomatic patients (13,69).…”
Section: Compared With Asymptomatic Covid-19 Patients Severely Ill Sy...mentioning
confidence: 73%
“…While the mechanisms that lead to severe COVID-19 remain to be fully elucidated, immune dysregulations are associated with the pathogenesis of COVID-19 including: (i) virus-specific adaptive immune responses that can trigger pathological processes characterized by localized or systemic inflammatory processes (7); (ii) increased levels of pro-inflammatory cytokines (8)(9)(10); and (iii) a broad lymphopenia (11)(12)(13)(14)(15)(16). Nevertheless, the role of CD4 + and CD8 + T cells in COVID-19 disease remains controversial (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). CD4 + and CD8 + T cells specific to SARS-CoV-2 have been reported to be associated with less severe symptoms (33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who evolve to the severe form of the infection have a high neutrophil/lymphocyte rate, acute pulmonary neutrophilic infiltration showing elevated serum cytokines, ferritin, hemophagocytosis, D-dimer, and soluble CD25 (the interleukin [IL]-2 receptor alpha chain). The presence of activated neutrophils and macrophages in the target tissues has been associated with induction of neutrophil extracellular traps (NETs) and thrombocytogenesis, promoting vascular collapse, respiratory distress, and multiorgan failure, which are related to the so-called cytokine release syndrome ("cytokine storm"), including excessive productions of granulocyte and macrophage colony-stimulating factor (GM-CSF), IL-2, IL-6, IL-7, IL-10, tumor necrosis factor α (TNF-α), and granulocyte colony-stimulating factor (G-CSF) [13]. We know that children respond better to viral infections, due to a trained immune system (both due to vaccines and recurrent infections).…”
mentioning
confidence: 99%
“…Low levels of type I interferons probably lead the immune system to compensate with unregulated activation of responses in the acute phase of infection, as exemplified by cytokine storm. In general, the predisposing factors for development of the cytokine storm consist of a diverse combination of mechanisms, involving viral escape associated with genetic defects of host defense, as well as other immunological abnormalities, such as high rate of neutrophil infiltration into target tissues [13]. Zhang et al identified deleterious mutations in IFN genes that impede their function in patients with the severe form of the disease.…”
mentioning
confidence: 99%